2023
DOI: 10.1177/00178969231191085
|View full text |Cite
|
Sign up to set email alerts
|

Canadian cannabis education resources to support youth health literacy: A scoping review and environmental scan

Emily J. Howe,
Lisa D. Bishop,
Bethany S. Torraville
et al.

Abstract: Background: The 2018 legalisation of cannabis in Canada sparked concern and conversation about the potential negative impacts of youth cannabis use. It is clear that young people are already engaging in cannabis use for a variety of reasons; therefore, youth cannabis education is desirable to promote harm reduction and reduce the risk of adverse physical and mental health outcomes. Objective: To identify and categorise Canadian cannabis education resources using a social-ecological approach informed by the you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The emergence of these programmes has been also influenced by policies such as the ‘War on Drugs’ 23. The abstinence-based model forms the basis of many programmes developed to prevent or treat problematic cannabis use and has been applied with at-risk or marginalised populations (eg, youth in the foster care system) 21 24. Despite its potential to decrease the frequency or amount of substance use, the abstinence approach presents limited evidence to support its effectiveness and has been criticised for various reasons 21 24–26.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of these programmes has been also influenced by policies such as the ‘War on Drugs’ 23. The abstinence-based model forms the basis of many programmes developed to prevent or treat problematic cannabis use and has been applied with at-risk or marginalised populations (eg, youth in the foster care system) 21 24. Despite its potential to decrease the frequency or amount of substance use, the abstinence approach presents limited evidence to support its effectiveness and has been criticised for various reasons 21 24–26.…”
Section: Introductionmentioning
confidence: 99%
“…The abstinence-based model forms the basis of many programmes developed to prevent or treat problematic cannabis use and has been applied with at-risk or marginalised populations (eg, youth in the foster care system) 21 24. Despite its potential to decrease the frequency or amount of substance use, the abstinence approach presents limited evidence to support its effectiveness and has been criticised for various reasons 21 24–26. First, it does not provide PWUC with the necessary skills to identify and mitigate the harms associated with their use 21 27.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of such resources, there are gaps in existing harm reduction cannabis education in Canadian schools [ 17 , 25 , 26 ]. Canadian provinces and territories are individually responsible for developing and providing health education, so there is no standardized cannabis education across the country [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a post-cannabis legalization qualitative study exploring youths’ cannabis health literacy, youth expressed dissatisfaction with the scare tactic messaging employed by abstinence-based education and reported learning little about cannabis in school, often obtaining information from social media or peers [ 17 ]. In a recent scoping review and environmental scan that identified Canadian cannabis education resources [ 25 ], many resources were identified but there were issues with accessibility, quality and multicultural considerations. Most education resources were not formally evaluated, and there was limited school-wide programming.…”
Section: Introductionmentioning
confidence: 99%